Femoral nerve palsy secondary to iliopsoas haemorrhage in patients with haemophilia: results from biceps femoral transfer (Colombia Medica, 2009)
Hemophilia causes injuries of peripheral nerves secondary to compressions by hematoma. In general, these injuries recover spontaneously after the cause of the compression is solved. A case of a 16-year-old adolescent with injury of the left femoral nerve, causing loss of the extension of the knee is described herein. During the evolution there was no recovery. For this reason a tendinous transfer of the femoral biceps was practiced. This technique was described formerly for the correction of poliomyelitis. Excellent results were obtained with complete recovery of the extension and force 4+/5.